2012
DOI: 10.1299/jtst.7.549
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Prototype Thermophotovoltaic Power Generation System Using Super-Adiabatic Combustion in Porous Quartz Glass

Abstract: A prototype thermophotovoltaic (TPV) generation system based on super-adiabatic combustion with reciprocating flow in porous media was developed experimentally. Stacked porous quartz glass plates in the system were used as an optical filter and for heat storage. The distributions of temperature and spectral radiation indicated that both energy recirculation and spectral control were realized with the quartz glass plates. In addition, electric power was obtained by introducing the spectral controlled radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…When considering the overall energy conversion (from chemical to electrical) efficiency, the calculated system efficiency at the maximum power condition for the best combustor configuration (quartz + SiC) is ∼0.08% (assuming that the radiation from both sides of the combustor are available to be harvested). This efficiency is similar to the reported value for a propane/air combustion driven TPV power generator [205], and is comparable to the values (0.03-0.15%) for a methane/air combustion powered TPV system [202]. TPV system with better efficiency was also reported.…”
Section: −34supporting
confidence: 89%
See 1 more Smart Citation
“…When considering the overall energy conversion (from chemical to electrical) efficiency, the calculated system efficiency at the maximum power condition for the best combustor configuration (quartz + SiC) is ∼0.08% (assuming that the radiation from both sides of the combustor are available to be harvested). This efficiency is similar to the reported value for a propane/air combustion driven TPV power generator [205], and is comparable to the values (0.03-0.15%) for a methane/air combustion powered TPV system [202]. TPV system with better efficiency was also reported.…”
Section: −34supporting
confidence: 89%
“…Therefore, the value of emitting area A SiC is taken as 1/4 × 50 mm × 50 mm = 625 mm 2 . Kumana and Hanamura [202] reported that in their prototype TPV system using porous media combustion, the temperature of the porous ceramics was measured to be over 1300 K under various flow conditions. Therefore, the porous foam peak temperature T SiC in this work is assumed in a reasonable range of 1200 -1500 K (higher than the maximum temperature of 1170 K on the quartz wafer outer surface as shown in Figure 6.8 (a)).…”
Section: −34mentioning
confidence: 99%